Synthesis and biophysical characterization of copper(ii) and molybdenum(v) tetrapeptides - Begum, Sharifa Zaithun (2015)
Metallopeptides have a lot of uses; however, they were questioned for their stability and cytotoxicity as well as their applications in catalysis. Five novel tetrapeptides (P1- P5) were synthesized using the Solid Phase Peptide Scheme (SPPS) and analysed with High Performance Liquid Chromatography (HPLC) and Liquid Chromatography-Mass Spectrometry (LC-MS) with percentage purities as high as 99.5%. Three of the peptides (P1-HAAD, P2-HAFD & P3-HAVD) had N-terminal protected with fluorenylmethyloxycarbonyl chloride (Fmoc) while the other two peptides (P4-AGHD & P5-PGHD) were not protected. All the peptides were positively charged (+1) and the molecular weight calculated from m/z value of MS results coincided with the theoretical molecular weight of the peptides. Metallopeptides derived from the five novel tetrapeptides with copper acetate monohydrate (MP1-MP5) and molybdenum chloride salts (MP6-MP10) in a 1:2 ratio were synthesised, purified and characterised by Ultraviolet-Visible (UV-Vis) spectroscopy, Ultraviolet-Fluorescence (UVFluorescence) spectroscopy and Fourier Transform Infrared (FTIR) spectroscopy, Circular Dichroism (CD) spectroscopy and optical rotation polarimetry. It provided the necessary information on the secondary structure, the successful binding of these two transition metals to the specific amino acids hence leading to the putative geometry of metallopeptides and the difference in the chirality of amino acids, peptides and metallopeptides. These metallopeptides were biophysically characterised and tested for their cytotoxicity against breast cancer cells and the cell proliferation of normal skin cells. After screening with two different breast cancer cells, MDA-MB-231 and MCF- 7, only two metallopeptides (MP2 & MP3) were deemed to have potential anticancer properties. The antimicrobial activity of P2 and MP8 were greater than ampicillin against Escherichia Coli (E.Coli). The catalytic activities of the synthesised complexes were evaluated. MP1 & MP3 catalysed both the asymmetric aldol reactions with high enantioselectivity of p-nitrobenzaldehyde with cyclohexanone (%ee = 87.3 & 80.3, respectively) and of p-anisaldehyde with cyclohexanone (%ee= 95.5 & 90.9, respectively).